Ditadura, memória e justiça : “revolução” e golpe de 1964 transitam no ciberespaço - Rocha, Luzimary dos Santos (2016)
The researching analyzes the Cyberspace as place of construction and preservation of memoirs conflicts related to civil-military dictatorship (1964-1985). The twentieth century brought many changes to the world in the political, social and economic context, but it also allowed the emergence of new technologies that have become creators of social relations becoming creators of new social practices. Technological advent favored the growth the means of mass comunication, highlighted among them the Internet that consolidated among societies becoming an entertainment space, means of communication, sociability network and propagator of ideologies and political behavior. From these considerations, this working aims to discuss the use of cyberspace as dissemination tool of political and ideological views corresponding the right and the left that are understand nowadays as political activism in defense or opposition to civil-military coup of 1964. Search in this context to understand also the persistence of the Right X Left categories in the current Brazilian society in the identification and analysis of social forces that have forms more complex of political organization. Beyond to these issues they were analyzed perceptions and demonstrative images of these aspects, including the policy of reparation of the Brazilian dictatorship crimes and the actions of the National Commission of the Truth. It is used as main sources, written texts and imagistic from sites of Terrorism Groups Never More (Ternuma / right) and Torture Never More (left), to identify and to clarify the objectives, ideologies and projects of society from current readings on the civil-military dictatorship.